Pelatihan Penggunaan Bahasa Kelas (Classroom Language) dalam Pembelajaran Bahasa Inggris Bagi Guru MAN Lombok Barat - Yuni Budi Lestari; Kamaludin Yusra; Nuriadi Nuriadi (Jurusan Pendidikan Bahasa dan Seni, FKIP, Universitas Mataram, 2023)
ABSTRAK Penggunaan bahasa kelas (Classroom Language) dalam proses pembelajaran bahasa Inggris sangatlah penting agar siswa terbiasa berkomunikasi dan berinteraksi dengan guru dan siswa lainnya di kelas secara lisan dan tulisan. Namun hanya sedikit guru bahasa Inggris yang bisa menggunakan bahasa kelas dengan efektif. Berdasrkan hal tersebut kegiatan pengabdian pada masyarakat bertujuan: 1). Untuk meningkatkan kemampuan penggunaan Classroom Language guru-guru Bahasa Inggris dan non-bahasa Inggris; 2). memecahkan salah satu permasalahan utama yang dihadapi guru-guru bahasa Inggris terkaiti rendahnya motivasi dan kemampuan siswa dalam berkomunikasi dan berinteraksi dalm bahasa Inggris.; dan (3) mengembangkan kerjasama antara Program Studi FKIP UNRAM dengan pemangku kepentingan terutama guru-guru bahasa Inggris di lingkungan MAN Lombok Barat.Metode yang digunakan dalam kegiatan pengadian ini adalah dengan presentasi untuk menyampaikan informasi tentang penggunaan Classroom Language di kelas, pemberian model, dan praktik atau latihan terbimbing dan mandiri. Jumlah peserta kegiatan yaitu 30 orang guru di lingkungan MAN Lombok Barat. ABSTRACT Using Classroom Language in the English learning process is so important that students get used to communicating and interacting with teachers and other students in class orally and in writing. However, only a few English teachers can use Classroom Language effectively. Based on this reason, this community service program aimed: 1) to improve the ability to use the Classroom Language of English and non-English teachers; 2) to solve one of the main problems that English teachers face related to students' low motivation and ability to communicate and interact in English; and (3) to develop collaboration between the English Education Department of the University of Mataram and stakeholders, especially English teachers in Islamic Senior High School of West Lombok. The method used in this program was by giving presentations to convey information about using Classroom Language in the classroom, providing models, and helping the teachers to use it in independent practice. 30 teachers from MAN Islamic Senior High School West Lombok and from other schools nearby participated. Based on the pretest, posttest, and observation of teaching practices, the results of this program indicate a significant improvement in the knowledge and skills of the participating teachers in using Classroom Language. Since Classroom Language is also highly beneficial as language input for students in the classroom, teachers should strive to maintain consistency in its usage.